(untitled) - Kowalski, Stefan J. (New York, 2003)
This book presents a systematic thermomechanical theory of drying with an interdisciplinary character, combining knowledge of chemical engineering with mechanics of continua. It contains a unified approach to the heat and mass transfer in drying processes, as well as a precise analysis of all local drying effects. Methods for the quality improvement of dried products and optimization of drying processes, with respect to the strength of materials and drying time, are presented. THERMOMECHANICS OF DRYING PROCESSES also presents the theory for fully coupled multiphase transport in deformable capillary porous media as well as computer simulations of drying processes. Finally the acoustic emission method is described as an experimental way of identifying material fractures during drying.
Keywords: Drying